Bamboo leaf ash for use as mineral addition with Portland cement - Silva, Lucas Henrique Pereira; Tamashiro, Jacqueline Roberta; Guedes de Paiva, Fábio Friol; Fernando dos Santos, Luis [UNESP]; Teixeira, Silvio Rainho [UNESP]; Kinoshita, Angela; Antunes, Patricia Alexandra (Elsevier, 2021)
In order to mitigate environmental impacts, get economic profitability, and produce materials, the industry has been incorporating some recycled waste into cement. In this work, bamboo leaf ash (BLA) was produced, characterized, and the feasibility of its use in mortar composition was analyzed, according to normative requirements. The chemical and physical characterization were performed with X-ray fluorescence, X-ray diffraction and laser granulometry. Compressive strength of mortar samples with replacement of 10, 20 and 30% wt% of cement by BLA was evaluated after 7, 28 and 91 days of cure. The pozzolanic activity of BLA was confirmed through Chapelle test, thermogravimetric analysis and X-ray diffraction. The results showed that up to 30% replacement of cement by BLA do not decrease the compressive strength of mortars. As this result meets the normative requirements, BLA is a potential material for the manufacture of cementitious materials, replacing partially cement. In addition, BLA has good cost-benefit and eco-efficiency, based on its life cycle analysis (LCA).
Keywords: Residue. pozzolanic materials. mortars. compressive strength